Mutational analysis of the BRCA1 gene in 30 Czech ovarian cancer patients - Zikan, M; Pohlreich, P; Stribrna, J (Journal of genetics, 2005)
Ovarian cancer is one of the most severe of oncological diseases. Inherited mutations in cancer susceptibility genes play a causal role in 5-10% of newly diagnosed tumours. BRCA1 and BRCA2 gene alterations are found in the majority of these cases. The aim of this study was to analyse the BRCA1 gene in the ovarian cancer risk group to characterize the spectrum of its mutations in the Czech Republic. Five overlapping fragments amplified on both genomic DNA and cDNA were used to screen for the whole protein-coding sequence of the BRCA1 gene. These fragments were analysed by the protein truncation test (PTT) and direct sequencing. Three inactivating mutations were identified in the group of 30 Czech ovarian cancer patients: the 5382insC mutation in two unrelated patients and a deletion of exons 21 and 22 in another patient. In addition, we have found an alternatively spliced product lacking exon 5 in two other unrelated patients. The 5382insC is the most frequent alteration of the BRCA1 gene in Central and Eastern Europe. The deletion of exons 21 and 22 affects the BRCT functional domain of the BRCA1 protein. Although large genomic rearragements are known to be relatively frequent in Western European populations, no analyses have been performed in our region yet.
Keywords: zárodečné mutace; DNA Mutational Analysis; Ovarian Neoplasms; Česká republika; geny BRCA1; Adult; Aged; dospělí; nádory prsu; senioři; nádory vaječníků; mutační analýza DNA; Czech Republic; Genes, BRCA1; Germ-Line Mutation; lidé; ženské pohlaví; Breast Neoplasms; Humans; Female; lidé středního věku; Middle Aged